Construction of a Dejourian theoretic model for the worker's health evaluation - Marilise Katsurayama; Rosana Cristina Pereira Parente; Rodrigo Otávio Moretti-Pires (Universidade de Fortaleza, 2012)
Objective: To construct a theoretical model intended for evaluative researches on the worker's health into the Family Health Strategy, supported by Christophe Dejours's theory. Methods: The theoretical model was built between September and December 2010, through the integration of Dejours's theory and the facts, the current situation of health workers, represented by official documents, which allowed the instrumentalization of thought, making affordable the features related to worker's health. Results: Dejourian theory was adopted as the basic element in the construction of this model, due to its approach to the dynamics of the mental processes involved in the confrontation between the subject and his reality in work, focusing the interest in the worker's subjective experiences (main source of pleasure and suffering in work). Given the influence played by the work organization on the worker's health, it becomes essential to perform the analysis of the variables that influence pleasure-suffering process among these actors of such an importance for the health practices that reorganize the primary care. Conclusion: Christophe Dejours's theory reveals its great potential for the analysis of the psychological processes involved in the confrontation between the worker in primary care and his reality, since it is vital to understand how the issues related to work in health area are disclosed, and the way the worker shall react to difficult work situations.